Propuesta de diseño urbano para la revitalización del espacio público en el oriente de la Ciudad de Neiva - Horta Alturo, Andrés Felipe; Puentes Saenz, Fredy Santiago (Universidad Antonio Nariño, 2023)
Huila, Neiva It is an intermediate city that has been overpopulated and disordered due to informal settlements of people affected by the armed conflict and the geography of the area, which has caused a variety of problems related to the lack of public space and accessibility problems, reflecting less vitality and urban cohesion; In light of the issues raised, sustainable urban development strategies are proposed, using land use planning tools to recover the layout of Carrera 52, which is the main axis of intervention in commune 10, where most of the population, cultural devices and intersections are located. The proposal includes the design of public spaces in the area from Carrera 52 in Las Palmas neighborhood to 30th street in El Tesoro neighborhood, as a structuring axis of commune 10, which seeks to address the main problems encountered and strengthen the identity of Neiva as a tourist corridor; it aims to connect all the industries near the proposal and meet the needs of people, preserving the identity, individuality and the seal of the city.